Thought-shape fusion in young healthy females appears after vivid imagination of thin ideals. (September 2016) - Wyssen, Andrea; Coelho, Jennifer S.; Wilhelm, Peter; Zimmermann, Grégoire; Munsch, Simone
Abstract: Background and objectives: It has been shown that exposure to female thin ideals in media has minimal to moderate direct effects on body image satisfaction (BIS), mood and dysfunctional eating in healthy young women. Evidence has been found for several intervening variables such as social comparison processes. Accordingly it is assumed, that cognitive processing (rather than mere media exposure) is crucial. Consequently, vivid imagination of thin ideals after exposure to a fashion magazine was induced in order to trigger cognitive processes. Changes in mood, BIS and resulting bodyrelated cognitive distortions (Thought-Shape Fusion Body, TSF-B) were assessed. Methods: A total of 91 healthy women (mean age 21.9 years, SD = 2.0) were exposed to either a fashion magazine (thin-ideal group) or a nature magazine (control group) in a waiting room design. Afterwards they were instructed to vividly imagine either the thin ideals or landscapes. Results: When exposed to thin ideals, a significant decrease in mood and BIS emerged after vivid imagination, but not after mere magazine exposure. Imagining thin ideals triggered body-related cognitive distortions (TSF-B). A higher degree of eating disorder (ED) symptomatology amplified this effect. Limitations: These findings apply to young healthy females and cannot be generalized to samples with obesity, EDs or males. Internal validity is limited since the intensity of the exposure has not been systematically controlled. Conclusions: Vivid imagination of thin ideals promoted by magazines results in impaired mood and BIS and moreover in body-related cognitive distortions (TSF-B) in healthy women, especially, for those with stronger ED symptomatology. Highlights: Exposure to a fashion magazine did not influence mood or body image satisfaction. Subsequent imagination of thin ideals had a negative impact on these variables. Imagination triggered cognitive distortions (thought-shape fusion body, TSF-B). Women with higher eating disorder symptomatology were more likely to reveal TSF-B.